Computer Simulations of Short Exposure Images of A single and Binary Star - Mohammed, A.; Tawfiq, A. (Iraqi Journal of Science, 2025)
The problem of atmospheric turbulence has taken a considerable amount of attentions in the literatures. Most of theise studies have not considering the quantitative aspects of the seeing conditions in terms of mathematical representation.The study involves two-dimensional computer simulations of short exposure recording using Kolmogorov approach. The quality of these images is quantified in order to see the effects of atmospheric turbulence on the observed images. This assessment shows clearly the parameters that affect the possibilities of approaching diffraction limiting resolution of the telescope.The results demonstrate that the average frequency components are linearly proportional to the square of the telescope radius and linearly proportional to the seeing conditions.Signal to noise and signal to background ratios of the autocorrelation function of a binary star as a function of telescope diameter and seeing conditions are calculated.